2021
DOI: 10.1038/s41598-021-99321-w
|View full text |Cite
|
Sign up to set email alerts
|

CTHRC1 expression is a novel shared diagnostic and prognostic biomarker of survival in six different human cancer subtypes

Abstract: According to the previous reports, the collagen triple helix repeat containing 1 (CTHRC1) causes tumorigenesis by modulating the tumor microenvironment, however, the evidence is limited to a few human cancer subtypes. In the current study, we analyzed and validated the CTHRC1 expression variations in 24 different human cancer tissues paired with normal tissues using publically available databases. We observed that CTHRC1 was overexpressed in all the 24 major subtypes of human cancers and its overexpression was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…Acknowledging the α-SMA +/- classification of myCAF activation, our analysis revealed that α-SMA was not a defining gene of our myCAF population, and we suggest that CTHRC1 may serve as a potential future marker for myCAF in PDAC and other solid tumor cancers due to its increased expression and positive contribution to the carcinogenesis of other cancers, such as stomach, liver, colon, and breast [47,48]. However, future studies will need to be conducted not only in PDAC, but in other cancers to validate CTHRC1 as a defining marker in myCAF.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Acknowledging the α-SMA +/- classification of myCAF activation, our analysis revealed that α-SMA was not a defining gene of our myCAF population, and we suggest that CTHRC1 may serve as a potential future marker for myCAF in PDAC and other solid tumor cancers due to its increased expression and positive contribution to the carcinogenesis of other cancers, such as stomach, liver, colon, and breast [47,48]. However, future studies will need to be conducted not only in PDAC, but in other cancers to validate CTHRC1 as a defining marker in myCAF.…”
Section: Discussionmentioning
confidence: 95%
“…To note, we did not conduct trajectory analysis and investigate the potential lineage of myCAF; however, studies done by Jin et al and Kang et al have revealed the function of CTHRC1 in activating pancreatic stellate cells (PSCs) [45], which are responsible for the differentiation of PSCs into myCAF [46], suggesting a potential cycle of differentiation into the myCAF indicated in our study. Acknowledging the α-SMA +/classification of myCAF activation, our analysis revealed that α-SMA was not a defining gene of our myCAF population, and we suggest that CTHRC1 may serve as a potential future marker for myCAF in PDAC and other solid tumor cancers due to its increased expression and positive contribution to the carcinogenesis of other cancers, such as stomach, liver, colon, and breast [47,48]. However, future studies will need to be conducted not only in PDAC, but in other cancers to validate CTHRC1 as a defining marker in myCAF.…”
Section: Discussionmentioning
confidence: 99%
“…Larger studies in HNSCC are needed to confirm the results. Secondly, CTHRC1 expression may not be a highly specific diagnostic and prognostic biomarker of HNSCC in humans, but be a shared diagnostic and prognostic biomarker of survival in different human cancers (23,24). These may limit its use in clinical diagnosis and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, upregulation of CTHRC1 results in a worse prognosis for patients with liver and epithelial ovarian cancers (19,23). Therefore, CTHRC1 can be considered a carcinogenic driving factor for the progression and metastasis of esophageal squamous cell carcinoma, and as a potential biomarker for prognosis and individualized treatment (20,24). It has been reported that CTHRC1 is involved in immune cell infiltration in the tumor microenvironment, has a pivotal role in the regulation of M2 macrophage polarization in ovarian tumors and is seen as a target for antitumor immunotherapy (25).…”
Section: Cthrc1 Is Associated With Immune Cell Infiltration and Funct...mentioning
confidence: 99%
“…CTHRC1 is known to be involved in tissue remodeling processes and closely associated with carcinogenesis and metastasis in solid tumors 25 . CTHRC1 has been shown to prompt gastric cancer metastasis via HIF-1α/CXCR4 signaling pathway 25 , and to be a common diagnostic and prognostic biomarker in six different human cancer subtypes, including STAD 26 . Highly expression of INHBA and activation of TGF-β signaling pathways were observed in GC tissues, and INHBA gene silencing inhibited the GC progression by inactivating the TGF-β signaling pathway 27 .…”
Section: Discussionmentioning
confidence: 99%